(untitled) (Eurasian Medical Research Periodical, 2024)
Alveolitis is the most common post-extraction complication [1–4]. The main symptoms of alveolitis appear 1–3 days after surgery [5, 6] and are pain of varying intensity in the area of the socket of the extracted tooth, as well as irradiation of pain to neighboring teeth, ear, and temporal region , in some cases - in the neck, eye and frontal area, loss of a blood clot, bad breath, increased temperature to subfebrile values, inflammation of the marginal edge of the gums, exposure of a fragment of the alveolar bone, a grayish coating on the walls of the socket, phenomena of regional lymph nodes ¬nit.